2014
DOI: 10.1007/s12010-014-1248-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced PC12 Cells Proliferation with Self-Assembled S-Layer Proteins Scaffolds

Abstract: Finding 3D biocompatible and biodegradable scaffold is important in tissue engineering which plays a critical role in transplanting methods. Several biomaterials, such as poly-L-lactide, poly(lactic-co-glycolic acid), poly(L-lactic acid)/poly(lactide-co-glycolide), alginate, collagen gel, and so on, have been applied as scaffold to culture cells in 3D environment. The most significant problem of the synthetic materials is lack of biocompatibility and bioactivity. Herein, self assemble S-layer proteins are used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Babolmorad et al (2015) reported that the viability of PC12 cells on the PLO 9% S-layer scaffold showed higher growth than the control (PLO-laminin) only after 24 hrs of cell seeding. 29 They could not do their experiments for more than 24 hrs. It may be due to the S-layer was not sterilized by formalin gas, so the scaffold might be contaminated.…”
Section: Cell-scaffolds Interaction and Metabolic Activitiesmentioning
confidence: 99%
“…Babolmorad et al (2015) reported that the viability of PC12 cells on the PLO 9% S-layer scaffold showed higher growth than the control (PLO-laminin) only after 24 hrs of cell seeding. 29 They could not do their experiments for more than 24 hrs. It may be due to the S-layer was not sterilized by formalin gas, so the scaffold might be contaminated.…”
Section: Cell-scaffolds Interaction and Metabolic Activitiesmentioning
confidence: 99%
“…Finally DF determines a general function that should be maximum following selection of optimum value of affective variables with consideration of their interaction . The main advantages of DFs are the ability to obtain qualitative and quantitative responses by simple and fast transformation of various responses for one measurement …”
Section: Methodsmentioning
confidence: 99%
“…[40,41] The main advantages of DFs are the ability to obtain qualitative and quantitative responses by simple and fast transformation of various responses for one measurement. [42]…”
Section: Experimental Designmentioning
confidence: 99%
“…A broad majority of these studies obtained an advantage of the topography imaging aspects of the technique. In them, the reported research showed the analysis of a large range of materials such as natural and synthetic polymers [52,53,54], collagen [55], silk fibroin [56,57,58], cellulose [59], peptides [60,61], graphene and carbon nanotubes (CNT) [62,63], particles [64,65], or patterned structures [66,67]. This list, kept short for compact design reasons, could include more field-related articles.…”
Section: Afm and Cell Scaffolds: Literature Reviewmentioning
confidence: 99%